The Emerging Role of the Thrombin Receptor (PAR-1) in Melanoma Metastasis - a Possible Therapeutic Target - Villares, Gabriel J. (Impact Journals LLC, 2011)
Melanoma remains as the deadliest form of skin cancer with limited and inefficient treatment options available for patients with metastatic disease. Within the last decade, the thrombin receptor, Protease Activated Receptor-1, has been described as an essential gene involved in the progression of human melanoma. PAR-1 is known to activate adhesive, invasive and angiogenic factors to promote melanoma metastasis. It is overexpressed not only in metastatic melanoma cell lines but is also highly expressed in metastatic lesions as compared to primary nevi and normal skin. Recently, PAR-1 has been described to regulate the gap junction protein Connexin 43 and the tumor suppressor gene Maspin to promote the metastatic melanoma phenotype. Herein, we review the role of PAR-1 in the progression of melanoma as well as utilizing PAR-1-regulated genes as potential therapeutic targets for melanoma treatment.